2022
DOI: 10.25122/jml-2022-0164
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of screening algorithms to identify persons with active pulmonary tuberculosis at prison entry: protocol of a systematic review and network meta-analysis

Abstract: Prison inmates are a high-risk group for tuberculosis (TB) infection and disease due to the increasing number of vulnerable fringe groups, risk factors (e.g., alcohol and drug addictions), contagious diseases (HIV, hepatitis), and their high-risk behavior. Compared to the general population, TB incidence and prevalence rates are significantly higher among prison inmates. Early identification of potentially infectious pulmonary TB (PTB) and targeted care of sick inmates are essential to effectively control TB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The pooled results showed that prisoners coughing ≥2 weeks were 0.08 times more likely to be infected with TB than their counterparts. Similarly, two studies 67,68 that looked at the length of coughing indicated that patients who coughed for 2 weeks or more had a higher risk of contracting the illness than patients who coughed for less time or did not cough. This is due to the fact that a TB patient's infectiousness is directly correlated with the quantity of tubercle bacilli that they discharge into the air.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled results showed that prisoners coughing ≥2 weeks were 0.08 times more likely to be infected with TB than their counterparts. Similarly, two studies 67,68 that looked at the length of coughing indicated that patients who coughed for 2 weeks or more had a higher risk of contracting the illness than patients who coughed for less time or did not cough. This is due to the fact that a TB patient's infectiousness is directly correlated with the quantity of tubercle bacilli that they discharge into the air.…”
Section: Discussionmentioning
confidence: 99%